Bacteriuria asintomática en mujeres embarazadas: frecuencia y factores de riesgo - Ginestre M; Martínez A; Fernández M; Alaña F; Castellano M; Romero S; Rincón G (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2001)
Abstract: Asymptomatic bacteriuria is a condition that favors the development of urinary infection during pregnancy and may be associated with adverse effects on maternal and fetal health. The risk factors that affect the frequency of bacteriuria include: age, number of pregnancies, gestational age, socio- economic status, anemia, and history of prior urinary infection. To determine the prevalence of a-symptomatic bacteriuria in a obstetric population, 101 midstream urine specimens from pregnant women who were treated in the ambulatory hospital "San Jacinto" from March to December 1999, were evaluated. Each specimen was tested by urine culture, Gram's staining, and pyuria. The prevalence was 13,86% (14/101). Escherichia coli was isolated in 7 (50,00%) specimens, followed to Klebsiella pneumoniae, Gardnerella vaginalis, and S. agalactiae, which were each obtained in 2 (14,28%) of the specimens. S. viridan groups were found in 1(7,16%) case. Gram's staining identified 11 (78,57%) positive specimens (sensitivity: 78,57%, specificity: 96,55%, PPV: 78,57%, and NPV: 96,45%); pyuria detected 9 (64,28%) cases (sensitivity: 74,28%, specificity: 91,95%, PPV: 56,25%, and NPV: 94,11%). To evaluated the relationship between a-symptomatic bacteriuria and the risk factors, an epidemiological survey was conducted. The statistical analysis indicated that in this population no significant correlation was detected between a-symptomatic infection and the variables studied. The prevalence of a-symptomatic bacteriuria in this population group indicate that the implementation of a detection program is necessary during the first three months of gestation. Resumen: Bacteriuria asintomática es una condición que favorece el desarrollo de infección urinaria en el embarazo y puede asociarse con efectos adversos en la salud materno-fetal. Los factores de riesgo que afectan la frecuencia de bacteriuria incluyen: edad, paridad, edad gestacional, estatus socioeconómico, anemia y antecedentes de infección urinaria. Para determinar la prevalencia de bacteriuria asintomática en una población obstétrica, se evaluaron 101 muestras de orina de embarazadas que asistieron al ambulatorio San Jacinto entre Marzo- Diciembre de 1999. Cada espécimen fue estudiado mediante urocultivo, coloración de Gram y detección de piuria. La prevalencia fue de 13,86% (14/101). Escherichia coli fue aislada en 7 (50,00%) muestras, seguida de Klebsiella pneumoniae, Gardnerella vaginalis y Streptococcus agalactiae, las cuales se obtuvieron en 2 (14,28%) especimenes, cada una. Streptococcus grupo viridans fue recuperado en 1 (7,16%) caso. La coloración de Gram identific ó 11 (78,57%) muestras positivas (sensibilidad: 78,57%, especificidad: 96,55%, VPP: 78,57% y VPN: 96,45%); piuria detectó 9 (64,28%) casos (sensibilidad: 74,28%, especificidad: 91,95%, VPP: 56,25% y VPN: 94,11%). Para evaluar la relación entre bacteriuria y factores de riesgo se aplic ó una encuesta epidemiológica. El análisis estadístico indica que en esta población no existe correlación significativa entre bacteriuria y las variables estudiadas. La prevalencia de bacteriuria asintomática en este grupo poblacional, indica la necesidad de implementar un programa de despistaje en el primer trimestre de la gestación.